2021
DOI: 10.2334/josnusd.21-0196
|View full text |Cite
|
Sign up to set email alerts
|

Micro CT pilot evaluation of removability of two endodontic sealers

Abstract: This study compared the removability of AH Plus and EndoSequence BC sealers using in vitro micro-computed tomography. Methods: Ten single-canal, extracted human teeth were cleaned and shaped with ProTaper NEXT rotary files to size X5 (50/0.06) (Dentsply-Sirona). Canals were obturated with a single cone gutta-percha and either AH Plus (Dentsply-Sirona) (Group A) or EndoSequence BC (Brasseler) (Group B). ProTaper Universal Retreatment files (Dentsply-Sirona) were used to remove obturation materials after 90 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…20 Several studies had previously documented resembling removal of both AH Plus sealer and Endosequence BC sealer. [21][22][23] Simsek et al found that there was no difference among the sealers including AH Plus and iRoot SP in terms of retreatment effectivenes. 24 On the contrary, in previous studies, it was observed that there was a larger quantity of RFM when using Endosequence BC sealer in comparison to AH Plus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Several studies had previously documented resembling removal of both AH Plus sealer and Endosequence BC sealer. [21][22][23] Simsek et al found that there was no difference among the sealers including AH Plus and iRoot SP in terms of retreatment effectivenes. 24 On the contrary, in previous studies, it was observed that there was a larger quantity of RFM when using Endosequence BC sealer in comparison to AH Plus.…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with the results of the Colmenar et al study, which also indicated that AH Plus and Endosequence BC sealers exhibited similar removability at all levels within the root canal. 21 Uzunoglu et al compared the elimination of iRoot SP, AH Plus, and MTA Fillapex. The quantity of RFM in the middle and lower third was comparable and greater than in the coronal thirds.…”
Section: Discussionmentioning
confidence: 99%
“…Initial root canal filling should be removed for the success of the retreatment procedure ( 22 ). The removal of a sealer is an important factor for endodontic retreatment because the sealer accounts for the greatest percentage of the remaining filling material on the canal surfaces after re-instrumentation ( 23 ).…”
Section: Discussionmentioning
confidence: 99%